Is there any impact of university-industry knowledge transfer on the performance of private enterprises? An empirical analysis based on Swiss firm data - Spyros Arvanitis; Nora Sydow; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2005)
This study investigates the impacts of a palette of Knowledge and Technology Transfer (KTT) activities (general information, educational and research activities, activities related with technical infrastructure, and consulting) (a) on several innovation indicators (a1) in the framework of an innovation equation with variables of endogenized KTT activities (overall activities, specific forms of activities) as additional determinants of innovation, and (a2) based on a matched-pairs analysis for several forms of KTT activities; (b) on labour productivity in the framework of a production function with endogenized KTT activities as an additional production factor. The data used in the study were collected by means of a survey of Swiss enterprises that took place at the beginning of 2005. We found that KTT activities improve the innovation performance of firms both in terms of R&D intensity and sales of innovative products. The positive effect of overall KTT activities can be traced back mainly to research and educational activities. This could be shown by several methods: the innovation equation approach with endogenized KTT variable as well as three matching methods. Further, KTT activities seem to exercise a positive influence on labour productivity both through a direct effect as well as through an indirect effect by raising the elasticity of R&D intensity with respect to labour productivity.
Keywords: O30; 330; knowledge and technology transfer; innovation activities; R&D activities; Forschungs- und Technologiepolitik; Wirkungsanalyse; Forschungskooperation; Industrielle Forschung; Schweiz